Integrated Water Resources Management Approaches to Improve Water Resources Governance - Juliet Katusiime (Water, 2020)
The water crisis can alternatively be called a governance crisis. Thus, the demand for good water governance to ensure effective water resources management and to attain specific water goals is growing. Many countries subscribe to the Integrated Water Resources Management (IWRM) approach to achieve this goal. The Integrated Water Resources Management approach aims to ensure a process that promotes the coordinated development and management of water, land, and related resources in a drainage basin to maximise economic and social welfare equitably without compromising the sustainability of vital ecosystems. The design of the Integrated Water Resources Management approach, including its pillars and principles, aspires to good water governance and effective resource management. However, empirical studies examining this hypothesis and analysing the impact of the Integrated Water Resources Management approach on water resources governance are limited, especially in developing countries. Therefore, we characterised and compared the water resources governance aspects of two catchments in Uganda’s Lake Albert basin. One of the catchments was exposed to integrated water resources management projects, while the other had no exposure to integrated water resources management projects. Some of the factors that supported the comparability of the two sites included spatial proximity linking into a related hydrological and social-economic setup, common water needs and belonging to the same water administration zone. Comparing both areas led us to analyse whether there was a difference in water resources governance actions, as well as in the quality of water resources governance, under the same overall water management and administrative zone. The data were based on field surveys using questionnaires and information guides in both catchments. The results show that the performance of water resources governance is markedly better in the catchment with Integrated Water Resources Management practices than the base catchment unaffected by these practices. Key themes examined include water resources governance styles, water resources governance systems presence, functionality, the performance of good governance principles, and water resources management effectiveness. The findings contribute to the aspirations for the promotion of integrated water management approaches for improved water resources governance, and the concept that the effectiveness of water resources management measures depends on governance effectiveness. Water governance is significant, as it spells out the power, rights, decisions, and priorities relating to given water resources and communities.